Lean manufacturing implementation in a plastic molding industry - Mohd Yusuff, Rosnah; A., Othman (2012)
Lean manufacturing is a set oftools and methodalogies that aims for the continuous elimination of wastes throughout the production cycle. This research addresses the implementation oflean principles and tools in a small and medium scale industry focusing on the Plastic Injection molding operation. The main target is to plan and test several strategies to eliminate waste on the shop floor. A systematic approach was used for the implementation of lean principles. This paper also describes the application of value stream analysis. The present and future states of value stream maps were constructed to improve the relevant production process by looking for opportunities to eliminate wastes and its sources and finally to improve the overall process flow. The implementation of VSM, 5S, SMED, Heijunka, Small lot size, Kanban, milkrun, layout and process improvement have shown very encouraging results. Productivity has increased to 94.1%, Delivery attainment increased to IOO%, Changeover time was reduced to 38.5 minutes and reduction in total inventory to 2.86 days. The implementation of lean manufacturing has proven to be effective and suitable for enabling a continuous improvement process.